Pengaruh Rasio Daging Buah Pala dan Gula terhadap Karakteristik Kimia dan Organoleptik Fruit Leather - Kuliahsari, Dessy; Syamsul, Muhammad Ayyub (Universitas Pahlawan Tuanku Tambusai, 2024)
His study evaluates the effect of the ratio of nutmeg flesh and sugar on the chemical and organoleptic characteristics of fruit leather. Three nutmeg flesh and sugar ratios were tested: A1 (70% nutmeg flesh, 30% sugar), A2 (50% nutmeg flesh, 50% sugar), and A3 (30% nutmeg flesh, 70% sugar) using a Completely Randomized Design (CRD). Organoleptic tests were conducted to measure color, aroma, texture, and taste, while chemical tests analyzed moisture content and pH. The results showed that the ratio of nutmeg flesh and sugar significantly affected texture and taste but did not significantly affect color and aroma. The best formulation was A3 with a moisture content of 9.58% and a pH of 3.25. This fruit leather formulation was the most preferred by panelists in terms of texture and taste, highlighting its commercial potential.